The Genethliacon of Barbara Bogołębska: On the Need of Celebrating Birthdays and Jubilees - Gaj, Beata (Following Rhetoric, Stylistics and Journalism. A Volume Dedicated to Professor Barbara Bogołębska, 2019)
The majority of popular Polish dictionaries of literary terms, which define even long-extinct and specific genres, ex. Japanese or Indian drama, probably do not contain any basic information on the genre, appearing in European (and not only) literature for at least 23 centuries until this day. Genethliakon is a confirmed genre since the times of Kallimach (3rd century B.C.), which honors the birth or anniversary of birth, sometimes of a lyrical, dramatized or rhetoric-epic nature. Nowadays, it is still cultivated in many languages of the world (also in Latin, accordingly to its tradition). This article shows progression of this genre in the European tradition. First birthday songs (most often by recalling the Apollonian connotations), connected the birth of man with light and poetry. What is particularly interesting, the basic features of genethliacon’s „genes” have not undergone significant changes over the centuries. Celebrating birth, anniversaries or other jubilees is still associated with wishes, offering gifts – including the creation of poetry. Perhaps such beautiful tradition is worth maintaining by giving someone a self-written song like… Genetliacon Barbarae Bogołębskae dedicatum.